NEOSCOPE: a randomised Phase II study of induction chemotherapy followed by either oxaliplatin/capecitabine or paclitaxel/carboplatin based chemoradiation as pre-operative regimen for resectable oesophageal adenocarcinoma. - Mukherjee, S; Hurt, C; Gwynne, S; Bateman, A; Gollins, S; Radhakrishna, G; Hawkins, M; Canham, J; Lewis, W; Grabsch, H; Sharma, R; Wade, W; et al. (2015)
BACKGROUND: Both oxaliplatin/capecitabine-based chemoradiation (OXCAP-RT) and carboplatin-paclitaxel based radiation (CarPac-RT) are active regimens in oesophageal adenocarcinoma, but no randomised study has compared their efficacy and toxicity. This randomised phase II "pick a winner" trial will identify the optimum regimen to take forward to a future phase III trial against neo-adjuvant chemotherapy, the current standard in the UK. METHODS/DESIGN: Patients with resectable adenocarcinoma of the oesophagus or Siewert Type 1-2 gastro-oesophageal junction (GOJ), ≥T3 and/or ≥ N1 are eligible for the study. Following two cycles of induction OXCAP chemotherapy (oxaliplatin 130 mg/m2 D1, Cape 625 mg/m(2) D1-21, q 3 wk), patients are randomised 1:1 to OXCAP-RT (oxaliplatin 85 mg/m(2) Day 1,15,29; capecitabine 625 mg/m(2) twice daily on days of RT; RT-45 Gy/25 fractions/5 weeks) or CarPac-RT (Carboplatin AUC2 and paclitaxel 50 mg/m2 Day 1,8,15,22,29; RT-45 Gy/25 fractions/5 weeks). Restaging CT/PET-CT is performed 4-6 weeks after CRT, and a two-phase oesophagectomy with two-field lymphadenectomy is performed six to eight weeks after CRT. The primary end-point is pathological complete response rate (pCR) at resection and will include central review. Secondary endpoints include: recruitment rate, toxicity, 30-day surgical morbidity/mortality, resection margin positivity rate and overall survival (median, 3- and 5-yr OS. 76 patients (38/arm) gives 90% power and one-sided type 1 error of 10% if patients on one novel treatment have a response rate of 35% while the second treatment has a response rate of 15%. A detailed RT Quality Assurance (RTQA) programme includes a detailed RT protocol and guidance document, pre-accrual RT workshop, outlining exercise, and central evaluation of contouring and planning. This trial has been funded by Cancer Research UK (C44694/A14614), sponsored by Velindre NHS Trust and conducted through the Wales Cancer Trials Unit at Cardiff University on behalf of the NCRI Upper GI CSG. DISCUSSION: Following encouraging results from previous trials, there is an interest in neo-adjuvant chemotherapy and CRT containing regimens for treatment of oesophageal adenocarcinoma. NEOSCOPE will first establish the efficacy, safety and feasibility of two different neo-adjuvant CRT regimens prior to a potential phase III trial. TRIAL REGISTRATION: Eudract No: 2012-000640-10. ClinicalTrials.gov: NCT01843829 .